Implementation of the Family Hope Program: Towards Indonesian Family Welfare - Riyadh, Ahmad; Dwi, Aditya Prima Yudha (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to analyze the implementation of the Family Hope Program (PKH) in Ganggang Panjang Village, Indonesia, and identify the factors that hinder or support its execution. Qualitative data was collected through purposive sampling and analyzed using Miles and Huberman's approach. The results reveal that the local PKH management was not involved in the selection of program beneficiaries, posing a significant challenge. Additionally, the lack of adequate transportation and facilities hindered the effectiveness of program facilitators. These findings underscore the need for greater local involvement in program decision-making and improved logistical support to enhance the program's impact on the target community.Highlight : The Family Hope Program (PKH) is a program launched by the Government of Indonesia in 2007 to break the chain of family poverty The local PKH management was not involved in the selection of program beneficiaries, posing a significant challenge The lack of adequate transportation and facilities hindered the effectiveness of program facilitators Keywords: Family Hope Program, implementation, Indonesia, factors, logistical support,Important aspects of the content